Global shape modeling using the OSIRIS-REx scanning Laser Altimeter. (1st November 2019) - Seabrook, J.A.; Daly, M.G.; Barnouin, O.S.; Johnson, C.L.; Nair, A.H.; Bierhaus, E.B.; Boynton, W.; Espiritu, R.C.; Gaskell, R.W.; Palmer, E.; Nguyen, L.; Nolan, M.; et al.
Abstract: The OSIRIS-REx Laser Altimeter (OLA) is a scanning lidar instrument with a high measurement rate of 10 kHz and a dexterous two-axis mirror. OLA is optimized for proximity operations ( < 7 km range) around a small asteroid. The high repetition rate and scanning capability of the instrument give OLA the ability to rapidly obtain high-density topographic scans of the surface of the near-Earth asteroid (101955) Bennu. We describe our approach to creating a global shape model using overlapping high-fidelity raster scans of the asteroid surface, demonstrated here with simulated data in advance of the asteroid encounter. This approach minimizes the dependence of the shape model on absolute position and pointing knowledge while taking advantage of the excellent short-term relative pointing stability of the instrument. It also provides a computationally efficient method of dealing with a dataset consisting of ≈ 1 billion data points through the use of keypoints and rigid transformations. The keypoint approach, in which matching features in overlapping scans are assigned a direct correspondence, mitigates against issues such as convergence into local minima, or dependence on initial conditions that methods such as ICP have. We explain how we generate maps, digital elevation models, and digital terrain models for determining the sampleability and safety of potential sample sites and for the scientific interpretation of the asteroid. Highlights: We use simulated altimetry data to demonstrate shape modeling of asteroid Bennu. Overlapping scans allow for correction of offsets due to spacecraft uncertainties. A "keypoint" or feature-matching approach is robust and computationally efficient. This approach allows global registration at accuracies near instrumental precision.